Effect of Wind Velocity on Transport and Distribution of Co2 Fluxes at a Tropical Location, Ile-Ife, Southwest Nigeria (Global Journal of Science Frontier Research, 2023)
This study investigated effect of wind velocity on CO 2 fluxes at a tropical location, Ile-Ife, southwest Nigeria. Half-hourly averaged flux data acquired by eddy covariance measurements conducted for a complete two-year period (2017-2018) over a grass-covered surface at Obafemi Awolowo University, Ile-Ife, Nigeria was analyzed. The results showed that CO 2 fluxes increased rapidly from sunset to sunrise due to stable boundary layer and nighttime soil respiration. Large transport of CO 2 fluxes was very prominent in the early morning when winds were strong and large air-masses leaving the site. Consequently, CO 2 concentration dropped as convective activities kicked off, enhancing photosynthesis. CO 2 flux and concentration exhibited good linear relationships with relative humidity but strong inverse correlations with temperatures and radiations at the site. The dominant wind flow in the area, southwesterly was largely responsible for transport and distribution of fluxes. The study concluded that wind velocity has little or no significant influence on the transport and distribution of CO 2 fluxes, particularly at nighttime. This may be attributed majorly to low frequency distribution of winds in the area.
Keywords: CO2 fluxes; wind velocity; frequency distribution; southwesterly; tropical location